Peran Wanita Dalam Usahatani Kopra Putih Di Desa Lameo-Meong Kecamatan Poleang Barat Kabupaten Bombana - Wahyuni, Syahri; Hisrah, Hisrah; Yunike, Lian; Helviani, Helviani; Juliatmaja, Aan Wilhan; Purbaningsih, Yuli; Nursalam, Nursalam (Musamus University, 2023)
This study aims to determine the role of women farmers in white copra farming in Lameo-Meong Village, West Poleang District. This study uses a qualitative approach where the research data is analysed descriptively and qualitatively. The results of the discussion show that women farmers in white copra farming activities in Lameo-Meong Village, West Poleang District are in the high category because, in addition to taking care of household chores which are the responsibility of a mother, women also play a role (helping husbands) in the process of white copra farming such as splitting coconuts, gouging out coconuts, melting coconuts, drying coconuts and closing the drying of white copra. Not only helping to increase the productivity of the agricultural sector but also generating added economic value for the local community. The active participation of women farmers has a positive impact on increasing social and economic welfare in rural areas. The role of women in copra farming is vital and must always be supported by all parties so that the development of this industry will progress and develop rapidly.